Little Princes : One Man's Promise to Bring Home the Lost Children of Nepal - Grennan, Conor (New York : William Morrow, 2010)
Describes how the author's three-month service as a volunteer at the Little Princes Orphanage in war-torn Nepal became a commitment for advocacy and reform when he discovered that many of his young charges were victims rescued from human traffickers.
Includes index
Keywords: Grennan, Conor -- Travel -- Nepal; Orphanages -- Nepal; Child trafficking -- Nepal